The effectiveness of ‘master the verbs’ Instagram flashcards among year six low proficiency level students / Dania Mardhiah Ismail and Kuldip Kaur Maktiar Singh - Ismail, Dania Mardhiah; Maktiar Singh, Kuldip Kaur (Academy of Language Studies, 2023)
It is vital that students understand verbs a soon as they begin studying English, and that teachers work hard to educate them in mastering them. With the help of Instagram verbs flashcards, it can be convenient and beneficial for students to learn and teachers to teach verbs effectively. The goal of this study is to see how effectively Instagram verbs flashcards work for low proficiency in English language students. This study’s participants included 40 students and 21 teachers. Data was collected quantitatively and qualitatively. A pre-test and post-test were also conducted to determine the effectiveness of the innovation for the selected low proficiency level Year 6 students. A questionnaire was distributed to the teachers and interviews conducted to gather their opinions regarding the usefulness of using Instagram flashcards in the classroom. The results showed that after using the Instagram flashcards, all 40 students’ scores increased. Feedback from the teachers’ questionnaire and interviews revealed that by using the Instagram verb flashcards, there was an improvement in students’ grammar proficiency level. In summary, the findings of this study showed the successful application of Instagram verb flashcards in improving verb proficiency of low proficiency students. The implication of the study is that the ‘Master the Verbs’ Instagram flashcards are beneficial as a teaching and learning tool to help students learn verbs.